Tillie Olsen: Working-Class Mother, Proletarian Writer and Feminist Forerunner - Ronald Paul (Moderna Språk, 2016)
In this article, I want to trace the interwoven pattern of relationships between Tillie Olsen’s life as a working-class mother, her radical political commitment as a socialist and feminist and her own fictional and non-fictional writing. I want to show that despite the fragmentary nature of her literary production, there is a tangible and essential link between her personal experience, her politics and her aesthetics as a modern proletarian writer. It is, I would claim, this combination of gender, class and radical consciousness that enabled her to produce some of the most remarkably unorthodox fictional narratives of working-class women’s lives in the whole of twentieth-century American literature.